AKU BERAGAMA, AKU ADA: PERSEPSI AKAN #AKSIBELAISLAM DALAM RANAH KONSEP SELF AND OTHER - Nuki Mayasari (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2017)
The Islamic Defense Movement movement had made headlines from various national media outlets in Indonesia. Although the last series of demonstrations, when this research was written, took place on December 2nd, 2016, the echoes of the Islamic Defense Action can still be seen in various opinions of internet users on social networks. This study discusses the perceptions behind internet users’ opinions of the action, using the Critical Discourse Analysis (CDA) method. Taking a sample of Twitter Twitter chants, the authors make a percentage of the main ideas behind the various opinions. As a result, the concept of self and other is the dominant idea behind the chirp with tagar #AksiBelaIslam . Keywords: Aksi Bela Islam, Twitter, Critical Discourse Analysis, Self, and Other